Early and late outcomes of emergency coronary bypass grafting in non-ST-segment elevation acute myocardial infarction - Nguyen Thai Minh; Nguyen Sinh Hien; Bui The Dung; Doan Quoc Hung (Italian Journal of Medicine)
The majority of patients undergoing emergency coronary artery bypass grafting for non-ST-segment elevation myocardial infarction are of advanced age and have many comorbidities, which pose challenges for operation. This study aimed to determine the early and midterm outcomes of this subgroup. The study conducted a retrospective analysis on 89 patients who experienced non-ST-elevation acute myocardial infarction and underwent emergency coronary artery bypass graft surgery at Hanoi Heart Hospital in Hanoi, Vietnam, between January 1, 2020, and December 31, 2022. The primary outcome variable was in-hospital mortality, and the secondary outcome variable was midterm mortality. The mean age of the cohort was 66.4 years. Female accounted for 31.46%. Over half of patients (53.9%) were operated on within 24 hours from the onset of symptoms. The average European System for Cardiac Operative Risk Evaluation (EuroSCORE II) was 10.55%. The number of coronary bypasses was 3.4. Aortic cross-clamp and cardiopulmonary bypass times were 64.2 and 94.4 minutes. The in-hospital mortality rate was 10.11%. Significant predictors determining in-hospital mortality were the EuroSCORE II score. The mean follow-up time was 28.2±12.2 months. Survival rates at 1 year and 2 years were 97.5% and 96.02%, respectively. Emergency coronary bypass surgery in patients with non-ST segment elevation myocardial infarction had poor early but good midterm outcomes. A high EuroSCORE II score was a predictor of in-hospital mortality.